2020
DOI: 10.1186/s41927-020-00122-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the interleukin-17 effect on articular cartilage in a translational model: an explorative study

Abstract: Background: Osteoarthritis (OA) is a progressive, chronic disease characterized by articular cartilage destruction. The pro-inflammatory cytokine IL-17 levels have been reported elevated in serum and synovial fluid of OA patients and correlated with increased cartilage defects and bone remodeling. The aim of this study was to characterize an IL-17-mediated articular cartilage degradation ex-vivo model and to investigate IL-17 effect on cartilage extracellular matrix protein turnover. Methods: Full-depth bovine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…Other reviews [ 139 , 140 ] have well described how articular cartilage explant models have used various types of injurious compression protocols to simulate mechanical injury and have demonstrated that, despite differences in protocols, these models show that they similarly and successfully induce the clinically observed pathologies following trauma to the knee joint. Hence, the mechanically-induced injury of articular cartilage leads to a significant increase in chondrocyte death, ECM loss, expression of matrix-degrading enzymes and a decrease in the COL2 gene and, to some extent, an increase in inflammatory cytokines even in the absence of inflammatory cells, such as macrophages [ 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 ]. Some studies have used a combination of mechanical injury and inflammatory cytokine treatment, typically using IL-1α, IL-1β, TNF-α, IL-17, or the combination of TNF-α/IL-6/sIL-6R [ 143 , 144 , 145 , 146 , 148 , 152 , 154 ] to mirror trauma and the presence of cytokines that are significantly present with the injured knee.…”
Section: Results Of the In Vivo Ex Vivo And In Vitro Models That mentioning
confidence: 99%
See 2 more Smart Citations
“…Other reviews [ 139 , 140 ] have well described how articular cartilage explant models have used various types of injurious compression protocols to simulate mechanical injury and have demonstrated that, despite differences in protocols, these models show that they similarly and successfully induce the clinically observed pathologies following trauma to the knee joint. Hence, the mechanically-induced injury of articular cartilage leads to a significant increase in chondrocyte death, ECM loss, expression of matrix-degrading enzymes and a decrease in the COL2 gene and, to some extent, an increase in inflammatory cytokines even in the absence of inflammatory cells, such as macrophages [ 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 ]. Some studies have used a combination of mechanical injury and inflammatory cytokine treatment, typically using IL-1α, IL-1β, TNF-α, IL-17, or the combination of TNF-α/IL-6/sIL-6R [ 143 , 144 , 145 , 146 , 148 , 152 , 154 ] to mirror trauma and the presence of cytokines that are significantly present with the injured knee.…”
Section: Results Of the In Vivo Ex Vivo And In Vitro Models That mentioning
confidence: 99%
“…This study, like other studies on articular cartilage explants, chondrocytes and/or synoviocytes suggest that IL-17 acts synergistically with IL-1β or TNF-α [ 152 , 153 , 169 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 ], potentiates inflammatory gene expression (e.g., IL-6, IL-8, TNF-α) and MMP expression, and causes catabolic effects, such as ECM component loss and a decrease in the mRNA expression of chondrogenic markers, such as SOX9, XYLT1, COL2A1, and ACAN. IL-17A also caused the release of MMP-2, and -9, sGAG, the ADAMTS-mediated aggrecan degradation fragment (exAGNx1) and MMP-mediated type II collagen (C2M) in a bovine full-depth articular cartilage [ 150 ]. Moreover, this study showed that the proteomic analysis of conditioned media from IL-17A treated articular cartilage revealed an upregulation of IL-6, MMP-3, ADAMTS-4, neutrophil/macrophage chemoattractants CXCL6 and CCL20 (also known as macrophage inflammatory protein-3 alpha, MIP-3α), complement factor B, latent TGF-β-binding protein 2 and chitinase 3-like 1 (CHI3L1 or YKL-40), a secreted glycoprotein linked to OA, compared to control-treated tissue.…”
Section: Results Of the In Vivo Ex Vivo And In Vitro Models That mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, IL33 has been reported to be linked with IL17 in terms of contributing to immunological dysfunction in inflammatory diseases [41,42]. The IL17 receptor is a complex that consists of IL17RA, IL17RB, IL17RC, IL17RD, and IL17RE [43]. IL17RA is a key component required for IL17A activity, and blocking of IL17 binding by IL17RA could inhibit the expression of IL-6 to prevent synovial inflammation in arthritis [44].…”
Section: Discussionmentioning
confidence: 99%
“…IL17RA is a key component required for IL17A activity, and blocking of IL17 binding by IL17RA could inhibit the expression of IL-6 to prevent synovial inflammation in arthritis [44]. A high expression of IL17A 7 Mediators of Inflammation contributes to cartilage degradation by inducing disintegrinlike and metalloproteinase with thrombospondin motifs (ADAMTS) protease and matrix metalloprotease in the articular cartilage in arthritis [43]. A high expression of IL17A was observed in the hyaline cartilage, and receptor IL17RA was evaluated with regards to hypertrophy chondrocyte (Figure 6).…”
Section: Discussionmentioning
confidence: 99%